Rare case of circumferential esophageal peeling. Issue 7 (13th April 2020) - Tominaga, Kentaro; Tsuchiya, Atsunori; Sato, Hiroki; Ishii, Yui; Takeda, Nobutaka; Natsui, Kazuki; Kawata, Yuzo; Kimura, Naruhiro; Arao, Yoshihisa; Takeuchi, Suguru; Hayashi, Kazunao; Yokoyama, Junji; et al.
Abstract: This report highlights the easy peeling of the esophageal epithelium with Nikolsky phenomenon after swallowing the foreign body and the healing status of the esophagus only 3 days later in a patient of pemphigus vulgaris. Abstract : This report highlights the easy peeling of the esophageal epithelium with Nikolsky phenomenon after swallowing the foreign body and the healing status of the esophagus only 3 days later in a patient of pemphigus vulgaris.